Experimental study on the effect of porous medium on performance of a single tube heat exchanger: A CO2 case study. Issue 6 (10th April 2013) - Tarawneh, Mohammad; Alshqirate, AbedAlrzaq; Khasawneh, Khaleel; Hammad, Mahmoud
Abstract An experimental study on single‐phase laminar forced convection in a single porous tube heat exchanger is presented. Parametric studies are conducted for different inlet pressures, different mass flow rates, and different porosities to evaluate the effects of particle diameter and Reynolds number on the heat transfer and friction factor. The Nusselt number and friction factor are developed for efficient design of a porous heat exchanger based on the present configuration. Heat is transferred to the walls of the heat exchanger by natural convection mode. Gravel sand with different porosities is used as a porous medium during the tests. The flow of carbon dioxide as a working fluid in the porous medium is modeled using the Brinkman–Forchheimer‐extended Darcy model. A dimensionless performance parameter is developed in order to be used in evaluating the porous tube heat exchanger based on both the heat transfer enhancement and the associated pressure drop. The study covers a wide range of inlet pressures (Pi), mass flow rates ( <![CDATA[$\dot{m}$]]> <inline-graphic xlink:href="ark:/27927/pgg2rgb0r3b" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />), porosity of gravel sand (ε), and particle diameters (dm) which ranged 34.5 ≤ Pi ≤ 43 bars, 8 ∗︁ 10−5 ≤ <![CDATA[$\dot{m}$]]> <inline-graphic xlink:href="ark:/27927/pgg2rgb0r2s" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> ≤ 16 ∗︁ 10−5 kg/s, 34.9% ≤ ε ≤ 44.5%, 1.25 ≤ dm ≤ 5.15 mm, respectively. This study revealed that a smaller particle diameter can be used to achieve higher heat transfer enhancement, but a larger particle diameter leads to a more efficient performance based on heat transfer enhancement. The average heat transfer coefficient of carbon dioxide decreases when the porosity increases. © 2013 Wiley Periodicals, Inc. Heat Trans Asian Res; Published online in Wiley Online Library (wileyonlinelibrary.com/journal/htj). DOI 10.1002/htj.21059